Strategies for successful student teaching : - Pelletier, Carol Marra (Allyn and Bacon, 2004)
From the first steps of student teaching to the first teaching position, the Second Edition of Strategies for Successful Student Teaching provides a comprehensive resource and guide for pre-service teachers beginning their student teaching or practicum experience. This text moves pre-service teachers through their practicum experiences sequentially, beginning with the question, "Why do you want to be a teacher?" It then progresses to the creation of a portfolio, tips for the job search, and a checklist for setting up a first classroom. The book has a hands-on approach, featuring practical activities that build on theory taught in methods courses and can be used in the field with college supervisors to strengthen the link between theory and practice.